Comprehensive ICF Core Set for Obstructive Pulmonary Diseases: validation of the Activities and Participation component through the patient's perspective. (24th January 2013) - Marques, Alda; Jácome, Cristina; Gabriel, Raquel; Figueiredo, Daniela
Abstract: Purpose: This study aimed to validate the Activities and Participation component of the Comprehensive International Classification of Functioning, Disability and Health (ICF) Core Set for Obstructive Pulmonary Diseases (OPD) from the patient's perspective. Methods: A cross-sectional qualitative study was conducted with a convenience sample of outpatients with Chronic Obstructive Pulmonary Disease (COPD). Individual interviews were performed and analysed according to the meaning condensation procedure. Results: Fifty-one participants (70.6% male) with a mean age of 69.5 ± 10.8 years old were included. Twenty-one of the 24 categories contained in the Activities and Participation component of the Comprehensive ICF Core Set for OPD were identified by the participants. Additionally, seven second-level categories that are not covered by the Core Set were reported: complex interpersonal interactions, informal social relationships, family relationships, conversation, maintaining a body position, eating and preparing meals. Conclusions: The activities and participation component of the ICF Core Set for OPD was largely supported by the patient's perspective. The categories included in the ICF Core Set that were not confirmed by the participants and the additional categories that were raised need to be further investigated in order to develop an instrument according to the patient's perspective. This will promote a more patient-centred assessments and rehabilitation interventions. Implications for Rehabilitation: The Activities and Participation component of the Comprehensive ICF Core Set for OPD is largely supported by the perspective of patients with COPD and therefore could be used in the assessment of patients' individual and social life. The information collected through the Activities and Participation component of the Comprehensive ICF Core Set for OPD could be used to plan and assess rehabilitation interventions for patients with COPD.